2005
DOI: 10.1089/dna.2005.24.299
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles of Sp Family Members in HIV-1 Tat-Mediated Manganese Superoxide Dismutase Suppression in Hepatocellular Carcinoma Cells

Abstract: The expression of manganese superoxide dismutase (MnSOD) is regulated by agents associated with cancer development. It has been shown that infection with the human immunodeficiency virus type 1 (HIV-1) is associated with the development of liver cancer and that the transactivating transcriptional factor (Tat) of human HIV-1 reduces the expression of MnSOD in several cell types. However, the role of Tat in the expression of MnSOD in hepatocellular carcinoma is unknown. Furthermore, the precise mechanisms whereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Redox imbalance is a critical factor in the HIV life cycle and well established consequence of HIV infection and oxidative stress is a unifying factor across a vast array of HIV associated co-morbidities. In previous studies, Tat has been demonstrated to have a repressive effect on SOD2 expression by proxy of altering Sp1/Sp3 binding to the proximal sod2 promoter [44], though the reliance on artificial promoter constructs as well as transformed cell lines has left an incomplete picture of how Tat may interact with these transcription factors and effect SOD2 in more physiologically relevant systems. Here, we have observed that Tat indeed alters Sp1/Sp3 activity and as such, modulates endogenous SOD2 expression in primary HPAEC.…”
Section: Discussionmentioning
confidence: 99%
“…Redox imbalance is a critical factor in the HIV life cycle and well established consequence of HIV infection and oxidative stress is a unifying factor across a vast array of HIV associated co-morbidities. In previous studies, Tat has been demonstrated to have a repressive effect on SOD2 expression by proxy of altering Sp1/Sp3 binding to the proximal sod2 promoter [44], though the reliance on artificial promoter constructs as well as transformed cell lines has left an incomplete picture of how Tat may interact with these transcription factors and effect SOD2 in more physiologically relevant systems. Here, we have observed that Tat indeed alters Sp1/Sp3 activity and as such, modulates endogenous SOD2 expression in primary HPAEC.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also demonstrate HIV-1 gp120 mediated ER stress and apoptosis in simian virus 40 transformed astrocytes (SVGA) (Shah et al 2016). HIV-1 transactivator of transcription (Tat) increases mitophagy, as measured by LC3 cleavage, and is associated antioxidant depletion, a sign of oxidative stress (De Simone et al 2016; Porntadavity et al 2005). Further, several antiretroviral drugs interfere with physiological mitochondrial function, contributing to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%